Pavlo Postolyuk. Creation of the State of Bohdan Khmelnyts’ky in creation of three voivodeships - Postolyuk, Pavlo (Young Scholars Grinchenko – Seton International Journal, 2021)
Pavlo Postolyuk. Creation of the State of Bohdan Khmelnyts’ky in creation of three voivodeships. Abstract. The article considers the main stages of Hetman Bohdan Khmelnytsky’s state administration at the beginning of the National Liberation War, which led to the creation of the so-called Bohdan Khmelnytsky Hetman State within three voivodships; Kyiv, Bratslav, and Chernigiv. The Hetman and his loyal allies built the Hetman State in accordance with their own vision and ideas, which they wanted to implement. That is why a comprehensive and scientific study of their ideas and priorities is valuable, hence the experience of state building in such complex conditions of the early modern period of the second half of the 17th century. From the very beginning of the National Liberation War, the political system of the Polish-Lithuanian Commonwealth began to collapse, but the formation of Ukrainian statehood on the basis of the traditions of Cossack self-government was extremely intense. Keywords: Bohdan Khmelnytsky, state formation, Hetman State, Kyiv, Bratslav, Chernigiv voivodshops, National Liberation War, agreement.